Analisis Bibliometrik Tren Penelitian Kemampuan Koneksi Matematika dalam Pendidikan Tahun 2020-2025 - Pakhrurrozi, Imam; Indrawati, Indrawati; Shantika, Evana Gina (Media Pendidikan Matematika, 2026)
This study aims to provide a comprehensive mapping of the global research landscape regarding students’ mathematical connection ability during the period of 2020–2025. The primary focus includes the distribution of publications, evolving research themes, and international collaboration patterns. The research employs a bibliometric analysis approach using VOSviewer software. Data was systematically retrieved from the Scopus database following PRISMA guidelines, resulting in a final sample of 864 articles within the Social Sciences domain for analysis. Publication volume showed a general upward trend, reaching a peak in 2024 with 177 articles. The United States, China, and Indonesia were identified as the leading contributors to the field. Keyword analysis reveals a significant thematic shift from traditional cognitive approaches toward the integration of digital technologies, computational thinking, artificial intelligence, and sustainability. The research network is multisentral; the United States and Spain possess the highest Total Link Strength (TLS = 42), acting as primary global hubs. Indonesia is recognized as a strategic regional node, facilitating research connections within Southeast Asia. Overall, these findings provide an empirical foundation for researchers and educators to understand the dynamics and future opportunities within the field of mathematics education